An Assessment of the Impact of HIV/AIDS on Economic Growth: The Case of Kenya - Maureen Were; Nancy N. Nafula (Center for Economic Studies and ifo Institute (CESifo), 2003)
HIV/AIDS pandemic in Africa has been closely associated with adverse economic effects, and could thwart the success of poverty reduction initiatives. HIV/AIDS is fast eroding the health benefits, which Kenya gained in the first two decades of independence. The paper explores the different channels through which HIV/AIDS affects economic growth in a low-income country like Kenya. Within this framework, the paper attempts to analyse the impact of HIV/AIDS on Kenya's economic growth by way of simulations using a macroeconomic model for the Kenyan economy. Some of the key channels explored are the impact of HIV/AIDS on productivity and labour force supply; asset accumulation of human, physical and social capital; and the gender channel.
Keywords: 330